Influence of alloying elements on mechanical and electronic properties of NbMoTaWX (X = Cr, Zr, V, Hf and Re) refractory high entropy alloys. (November 2020) - Tong, Yonggang; Bai, Linhui; Liang, Xiubing; Chen, Yongxiong; Zhang, Zhibing; Liu, Jian; Li, Yejun; Hu, Yongle
Abstract: NbMoTaW refractory high entropy alloy (RHEA) has shown great potential applications for high temperature components due to its high temperature mechanical strength. However, the brittleness at room temperature hinders its engineering application and further development. To overcome this deficiency, refractory alloying elements with melting temperatures over 1850 °C, i.e., Cr, Zr, V, Hf, and Re, were chosen to enhance the mechanical performance of NbMoTaW RHEA in the present work. The effects of refractory alloying elements on the strength and ductility of NbMoTaW RHEA were investigated via a combination of theory and experiment. To be specific, the first-principle calculations based on density functional theory were employed to predict the mechanical properties of the alloyed NbMoTaWX (X = Cr, Zr, V, Hf and Re) RHEAs and explain the alloying effect from the atomic and electronic level. Moreover, the phase structures of the alloyed RHEAs were determined based on the formation enthalpy and cohesive energy, as well as some empirical parameters, such as the average valence electron concentration VEC and atomic size difference δ . In combination with the experimental results, the calculated elastic constants and modulus indicated that most of these alloying elements enhanced the strength of NbMoTaW RHEA, while only Zr-alloying significantly improved the ductility. The strengthening mechanism of different elements was well analyzed based on the total and partial density of states, overlapping Mulliken population, charge density contour, and atomic distance. The improvement of the ductility for Zr-alloying was attributed to the formation of Zr–Zr metallic bonds in the alloyed NbMoTaWX RHEAs. The theoretic predictions were confirmed by the experimental investigations. The present work provides a good guidance for design and construction of NbMoTaW RHEA. Highlights: Mechanical properties of alloyed NbMoTaW RHEA were investigated based on first-principle calculation and experiments. Cr, Zr, V, Hf and Re enhance the alloy' strength, while only Zr alloying improved both ductility and strength. V, Cr, Hf and Re strengthening of NbMoTaW RHEA should be attributed to the stronger atomic interaction. Zr-Zr metallic bonds formed in the Zr-alloyed RHEA help to improve both the strength and ductility.